Children's reading skills: The role of parental involvement in elementary school education - Roy Gustaf Tupen Ama; Rufina Nenitriana S Bete; Maria Regina Jaga (Universitas Sarjanawiyata Tamansiswa, 2025)
Reading skills are fundamental to reading and must be possessed by students, especially elementary school students, as preparation for success in reading. The purpose of this study was to determine the effect of parents' perceptions of involvement on the reading skills of elementary school students. The research method used in this study was quantitative with statistical analysis. The research subjects in this study were elementary school students at Catholic School